A boron, nitrogen-containing heterocyclic carbene (BNC) as a redox active ligand: synthesis and characterization of a lithium BNC-aurate complex. Issue 20 (10th May 2022) - Kimura, Yoshitaka; Lugo-Fuentes, Leonardo I.; Saito, Souta; Jimenez-Halla, J. Oscar C.; Barroso-Flores, Joaquín; Yamamoto, Yohsuke; Nakamoto, Masaaki; Shang, Rong
Abstract : A highly π-withdrawing boryl-substituted N-heterocyclic carbene ( Cl BNC) was generated at a gold(i ) center, which allowed a 2e − reduction to form a 6π BNC-aurate complex, showing the redox active nature of the diboron containing carbene ligand. Abstract : Stabilization of low oxidation gold anions as aurate or auride by organic ligands has long been a synthetic challenge, owing to the proneness of low-valent gold centres to cluster. Despite being the most electronegative metal, isolable gold(i ) aurate complexes have only been obtained from a few σ-withdrawing organo- and organo-main group ligands. Stabilization of highly-reduced gold complexes by π-modulating redox active ligands has only been achieved by cyclic (amino)(alkyl)carbene (CAAC), which is limited to 1e − -reduction to form neutral gold(0) complexes. This work reports a simple modular synthesis of a boron, nitrogen-containing heterocyclic carbene ( Cl BNC) at a gold(i ) center through metal-assisted coupling between azadiboriridine and isocyanides. The anionic electrophilic Cl BNC ligand in the gold(i ) complex [( Cl BNC)AuPMe3 ] (3a and 3b ) allows a 2e − -reduction to form the first η 1 -carbene aurate complex [(BNC)AuPMe3 ]Li(DME) (5a, DME = dimethoxyethane). Single crystal crystallographic analysis and computational studies of these complexes revealed a highly π-withdrawing character of the neutral 4π B, N-heterocyclic carbene (BNC) moiety and a 6π weakly aromatic character with π-donating properties to the gold(i ) fragment in its reduced form, showcasing the first cyclic carbene ligand that allows electronic tunability between π-withdrawing (Fischer-type)- and π-donating (Schrock-type) properties.